Fiber damage and impregnation during multi‐die vacuum assisted pultrusion of carbon/PEEK hybrid yarns. (24th February 2018) - Lapointe, Felix; Laberge Lebel, Louis
Abstract : Pultruded thermoplastic composites combine great mechanical properties with efficient manufacturing. However, the use of carbon commingled yarns as precursors presents two challenges: the damage induced by the process on the low ultimate strain carbon fibers and the impregnation of the fiber bed by the high‐viscosity matrix. The study outlines four major factors influencing the fiber damage: the carbon yarn tension, types of hybrid yarn used; the usage of a contact preheater and the tapered length of the pultrusion die. The yarn tension is identified as the most important parameter lowering the yarn damage. A tension of 3 N per yarn was adequate to reduce yarn damage. Two techniques are suggested as means to promote impregnation: the usage of multiple subsequent dies and the usage of vacuum. The effects of the die temperature and the pulling speed are also investigated. Void content of 1.3% was reported for the pultrusion of carbon/PEEK commingled yarns. The manufacturing parameters were four dies, vacuum, a speed of 50 mm/min, and a die system temperature of 400°C. POLYM. COMPOS., 40:E1015–E1028, 2019. © 2018 Society of Plastics Engineers